Presence of Feminism in Jhumpa Lahiri’s Fiction Works - Sharma , Tripti (International Journal of Psychosocial Rehabilitation, 2020)
The current paper targets recognizing the parts of Indian diasporic womanism in the chose works of Jhumpa Lahiri, a Bengali-American lady essayist. It acquires the expression "womanism" from Alice Walker and spotlights on the three vital parts of womanism: feminism, womanhood and parenthood. The review investigations the three significant works of Jhumpa Lahiri, The Interpreter of Maladies, an assortment of nine brief tales, which got her the Pulitzer Prize,The Namesake, a novel, which was made into a film, and the Unaccustomed Earth, an assortment of eight brief tales, which won her the Frank O‟ Conner Prize, and distinguishes an amazing number of settings to outline every part of Indian diasporic womanism. Lahiri best epitomizes the family centeredness of Africana womanism, the most completely expressed hypothesis of womanism to date, in her accounts of BengaliAmerican families, whose individuals well portray both physical and social maternity, an incredible principle of womanism as characterized by womanism researchers Chikwenye Okonjo Ogunyemi and Clenora Hudson-Weems. This paper likewise displays that lahiri mentality of feminism is not quite the same as other Indian postmodern women's activist scholars, since, her works are regarding Indian outsiders in far off nations.